Prevent major incident installation using consequence based method: article - Ibrahim, Illia Shahira; Abdul Rashid, Zulkifli (2019)
The aim of this paper is to identify the consequences of the LPG explosion towards the surrounding area and to compare the land-use restriction imposed by different countries with the result obtained. The consequences were calculated by using the static model of BLEVE and the overpressure. Askolani LPG storage facilities has been selected to perform a case study. The result obtained from the thermal radiation and overpressure calculation has allowed a comparison of different LUP criteria and have been used to evaluate the consequence of the explosion. From the comparison, it can be seen that the threshold limit value obtained from the ALOHA US EPA and the threshold limit value of French Guideline is much similar compared to the other two guideline. Thus, it is the best way to address the safety distance and lethal effect resulting from the studied scenario.